Simulation studies of shear stresses in reinforced and non-reinforced concrete structures (2009)
A simulation study of the shear stresses in non-reinforced and reinforced structures was carried in this work. Using the finite element method and equations of elasticity, columns and concrete deck of a simple storey structure were subjected to plane strian conditions. The results showed that proper reinforcement causes stresses to be directed into the reinforcements with the resultant transverse shear at critical joints of the structure. In the insufficiently reinforced member, the resultant shear of the concrete resulted in load transfered to the reinforcement itself with the resultant buckling of reinforcement and eventual collapse of structure.